2010 5th International Symposium on Telecommunications 2010
DOI: 10.1109/istel.2010.5734155
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling earth observation activities in LEO satellites using graph coloring problem

Abstract: Scheduling system of low earth orbit (LEO) satellite operations is one of the important tasks performed in satellites. Satellite specific constraints, satellite priorities, revenue of certain payloads and special operations, as well as visibility conflicts are taken into consideration while generating the operations schedules in an optimum way. This paper uses graph coloring problem for earth observation satellite scheduling, where as earth observing operations have to be scheduled on several resources while r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Zufferey et al [19] adapted the best ingredients of the graph coloring techniques to the NP-hard satellite range scheduling problem, called MuRRSP, then a tabu search and an adaptive memory algorithm were designed to tackle it. Sarkheyli et al [20] followed this line in investigating the scheduling system of low earth orbit (LEO) satellite operations. Wang et al [21] firstly introduced the theory of complex networks and found similarities between AEOS redundant targets scheduling problem and the node centrality ranking problem, then proposed a fast approximate scheduling algorithm (FASA) to obtain effective scheduling results.…”
Section: Introductionmentioning
confidence: 99%
“…Zufferey et al [19] adapted the best ingredients of the graph coloring techniques to the NP-hard satellite range scheduling problem, called MuRRSP, then a tabu search and an adaptive memory algorithm were designed to tackle it. Sarkheyli et al [20] followed this line in investigating the scheduling system of low earth orbit (LEO) satellite operations. Wang et al [21] firstly introduced the theory of complex networks and found similarities between AEOS redundant targets scheduling problem and the node centrality ranking problem, then proposed a fast approximate scheduling algorithm (FASA) to obtain effective scheduling results.…”
Section: Introductionmentioning
confidence: 99%